A toolset for handling unstructured voronoi grids for MODFLOW. (January 2023) - Bonduà, S.; Bortolotti, V.; Macini, P.; Strpić, K.
Abstract: MODFLOW is a modular hydrologic model developed by the United States Geological Service since 1984. The last version, MODFLOW 6, allows the use of finite volume (FV) general unstructured grid approach to solve the groundwater flow equations. The FV method entails constraints that are implicitly satisfied by a Voronoi discretization. In this paper, new versions of the freeware VORO2MESH and TOUGH2Viewer tools are presented for Voronoi grid generation for MODFLOW. Originally developed for the TOUGH family of codes, both software has been improved to also work with MODFLOW. VORO2MESH and TOUGH2Viewer have been applied to two case studies and the results have been compared with analytical solutions. Outcomes have demonstrated that VORO2MESH grids give simulation results very close to locally refined Grids created using the Quadtree approach; furthermore, the simulation activities are substantially enhanced using TOUGH2Viewer. Highlights: New pre and post processing tools for MODFLOW-compliant Voronoi grids are presented. VORO2MESH allows the generation of unstructured MODFLOW-compliant Voronoi grids. TOUGH2Viewer allows visualization of MODFLOW simulations performed on Voronoi grids. TOUGH2Viewer allows the export of MODFLOW results to PARAVIEW.